2015
DOI: 10.1097/bcr.0000000000000089
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Controlled Trial Comparing Two Methods of Securing Skin Grafts Using Negative Pressure Wound Therapy

Abstract: Negative pressure wound therapy (NPWT) has revolutionized the management of complicated wounds and has contributed an additional modality for securing split thickness skin grafts (STSG). The standard for NPWT is the vacuum-assisted closure (VAC) device. The authors' institution has accumulated experience using standard gauze sealed with an occlusive dressing and wall suction (GSUC) as their primary mode for NPWT. The authors report a randomized controlled trial comparing the efficacy of the GSUC vs the VAC in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 15 publications
0
18
0
1
Order By: Relevance
“…Eventually, several prospective and randomized studies were performed to formally compare the efficacy of this method to the VAC system, which demonstrated therapeutic equivalence. 18,19,27 In a prospective randomized trial of 87 patients from 2006 to 2008, Dorafshar et al (July 2012) demonstrated therapeutically equal efficacy of GSUC dressings when compared to that of commercialized VAC. Outcomes were primarily compared in respect to changes in wound surface area and volume over time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Eventually, several prospective and randomized studies were performed to formally compare the efficacy of this method to the VAC system, which demonstrated therapeutic equivalence. 18,19,27 In a prospective randomized trial of 87 patients from 2006 to 2008, Dorafshar et al (July 2012) demonstrated therapeutically equal efficacy of GSUC dressings when compared to that of commercialized VAC. Outcomes were primarily compared in respect to changes in wound surface area and volume over time.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative results were demonstrated with 96.12% in the GSUC group and 96.21% in the VAC arm. 19 Given the simple, inexpensive component materials used for the method, these studies also demonstrated great potential for cost savings even just on a per diem, per therapy basis. With that, the next natural progression was to review the long-term cost savings at an institutional level, as we have done here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NPWT requires fewer dressing changes and less resource use than standard dressings. If split‐thickness skin grafting of the fasciotomy is necessary, it may be preferable to use the less adherent polyvinyl alcohol dressing (white foam) as a wound filler on top of the split‐thickness skin graft.…”
Section: Negative‐pressure Wound Therapy For Lower Leg Fasciotomymentioning
confidence: 99%